ADULTS – CHILDREN POWER RELATIONS IN JUDY BLUME'S BLUBBER - Kurnia, Nandy Intan; Purbani, Widyastuti; Sugiarto, Tri (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2021)
(Tittle: Adults-Children Power Relations in Judy Blume's